A records management policy and file plan for the Versatile Instrumentation System for Science Education and Research (VISSER) project - Rodelas, Hazel Mary R. (School of Library and Information Studies, University of the Philippines Diliman, 2015)
It is important for government agencies and organizations, in general, to have a records management system to ensure that records are classified and organized. This study developed a records management policy and file plan for VISSER, a multi-million and multi-disciplinary project funded by the Department of Science and Technology.